Steady shear rheological characteristics of model system meat emulsions: Power law and exponential type models to describe effect of corn oil concentration - Karaman, Safa; Yilmaz, Mustafa Tahsin; Kayacier, Ahmed; Dogan, Mahmut; Yetim, Hasan (SPRINGER INDIA, 2015)
The effect of oil concentration (57.50, 58.75, 60.00 and 61.25 %) and temperature (5, 10 and 15 degrees C) on steady shear rheological properties of O/W model system meat emulsions were investigated. The effect of temperature and oil concentration was modeled using power law and exponential type functions. The meat emulsions showed non-Newtonian flow behavior because flow behavior index was lower than unity. Consistency coefficient and flow behavior index values of O/W model system meat emulsions were calculated using Oswald de Waele model with higher coefficients of determination. Apparent viscosities of emulsions at a specified shear rate (50 s(-1)) were in the range of 0.652-0.941 Pa s. Increasing oil concentration provided an increase in apparent viscosity and increase in temperature levels resulted a decrease in consistency coefficient values. The exponential function performed better than the power-law function (R-2>0.922) in terms of describing the effect of oil concentration on the steady shear rheological properties of the model system meat emulsions. Higher coefficients of determination (R-2=0.979-0.999) were observed in exponential-type function compared to a power law function (R-2=0.880-0.946).
Keywords: Meat emulsion; Rheology; Apparent viscosity; Temperature; Concentration; APPARENT YIELD-STRESS; FLOW PROPERTIES; FAT-CONTENT; VISCOSITY; MIXTURES; PROTEINS; SAUSAGES; BEHAVIOR; STARCH; Food Science & Technology